Career adaptability among FTTE students at Jambi University - Ramadhoni, Sri Rahmah; Wahyuni, Hera; Zubaidah, Zubaidah; Handoko, Yudo; Soleha, Siti Nahdhiatus (Universitas Islam Negeri Raden Intan Lampung, 2024)
Career adaptability is essential for students to navigate future career challenges effectively. It equips individuals to adjust to changes in the workplace and proactively manage their professional paths. This study examines the career adaptability of students at the Faculty of Teacher Training and Education (FTTE), Jambi University, involving 17 male and 157 female participants through a cross-sectional survey and quantitative descriptive approach. Data were collected using a career adaptability instrument and analyzed with descriptive statistics, t-tests, and independent t-tests. Simple random sampling was employed to select participants. The findings indicate that FTTE students generally exhibit moderate levels of career adaptability. Furthermore, t-test results (p = 0.00 < 0.05) reveal significant differences in career adaptability between male and female students. Interventions are recommended to include career counseling, guidance, training, and workshops to improve students' career adaptability.